Enlightenment and movement of teaching ideas in the hispanic monarchy - Perrupato, Sebastián (2018)
Studies on the Spanish Enlightenment have gone through two well differentiated paths. On one hand, a foreign tendency that understood that the true lights came from the French influence, and on the other hand, a group of historians that pretended to see in the Catholic component a certain originality. The two lines of work neglected the complex phenomena of appropriation and hybridization that occurred in modern Europe as a correlate of the circulation of ideas which tended to intensify during the eighteenth century. This paper attempts to analyze the flow of ideas around the educational proposals of the Spanish Enlightenment. Most Spanish intellectuals of the eighteenth century coincided in the need to articulate networks of dialogue and communication between the different parts of the globe, however for this they had to face several difficulties, censorship, translation and the scarcity of books are just some of them.